Amma La: Reflective Account of a Participatory Mixed Theatre Method in Migration Research in India - Lidis Garbovan (Journal of Participatory Research Methods)
This article presents the methodological process of interpreting the ethnographic data of my research about the question of Indian citizenship for Tibetan refugees in India as a theater play titled “Amma la” (meaning “mother” in Tibetan). I present the enacting of the theater play “Amma la” with young Tibetans in India (2019) at three different institutions. I argue that performing the theater play “Amma la” with Tibetan participants in 2019 is a method of enacting the research findings in a participatory, collaborative, creative, and novel way that opens up possibilities for shared meanings and transformative re-interpretation of the data within an embodied, artistic, and performative dimension. I argue that the performance of the theater play “Amma la” sits theoretically at the intersection of verbatim theater, political theater, and participatory drama as well as forum theater and physical theater. It could also be argued that the theater play “Amma la” constitutes a form of experimental theater that is not complete and foreclosing, but processual and prospective. And finally, performing “Amma la” is a form of process drama, focusing on improvisation, and the process of creating and acting a scene for the benefit of the participants-actors, and not on the polished and rehearsed performances for a specific audience. For these reasons, I argue that “Amma la” is constructed on and theoretically supported by what I will simply call participatory mixed theater methods.